White Fang - London, Jack; Adams, Richard (London : Puffin Books, 2016)
Born in the wilds of the freezing cold Yukon, the wolf cub White Fang soon learns the harsh laws of nature, growing fiercer and more independent in his struggle to survive. Yet buried deep inside him are distant memories of affection and love. Can he learn to trust man again?
Keywords: Action and adventure fiction; Dogs Juvenile fiction